Genetic and phenotypic parameters of growth traits in Muzaffarnagari sheep - GOPAL DASS; AJOY MANDAL; P K ROUT (Indian Journal of Animal Sciences, 2014)
Data on 2,540 Muzaffarnagari lambs born during 1992– 2006 at CIRG were recorded to study growth traits and genetic and phenotypic parameters. Sex and period of lambing had highly significant influence on all the body weights and average daily weight gains except significant effect on 6-and-9-month body weights. Season of birth showed significant influence on 6-and-9-month weight and on all ADGs except ADG during 0–3 month age group. Male lambs gained higher weight than female lambs at all the growth stages while year of lambing did not show any definite trend. Dams’ weight at lambing showed highly significant influence on birth and 3-month-body weight. Maximum growth of lambs (around 44%) was recorded during 0–3 month (pre-weaning) age followed by 3–6, 9– 12 and 6–9 age groups. This period of growth may be considered very crucial and should be ensured with proper management, feeding and health care for better productivity. Moderate to high genetic correlations of birth weight with subsequent weights indicated that selection of animals at early age will bring genetic improvement at later growth stages.